An initiative to evaluate the safety of maternal bonding in patients with SARS-CoV-2 infection. (17th September 2022) - Cojocaru, Liviu; Crimmins, Sarah; Sundararajan, Sripriya; Goetzinger, Katherine; Elsamadicy, Emad; Lankford, Allison; Turan, Ozhan M.; Turan, Sifa
Abstract: Background: In the last two decades, the world faced three epidemics caused by novel coronaviruses, namely, SARS-CoV in 2002, MERS-CoV in 2012, and the ongoing SARS-CoV-2 that started in late 2019. Despite a growing understanding of SARS-CoV-2 virology, epidemiology, and clinical management strategies, other aspects, such as mode of delivery, vertical transmission, and maternal bonding, remain controversial. The question we faced upon the decision to separate the neonates of SARS-CoV-2 positive mother is whether we follow the principle of "do no harm"? Methods: This is a quality improvement project that analyzed all cases of SARS-CoV-2 positive pregnancies that delivered at a major health care system from March 1, 2020 to June, 1 2020. The article was prepared following Standards for Quality Improvement Reporting Excellence (SQUIRE) 2.0 guidelines. Data were prospectively collected and entered into the Research Electronic Data Capture (REDCap). Maternal bonding was defined by events such as rooming-in, skin to skin contact (STSC), and breastfeeding. Descriptive analysis was performed using the same software platform. Intervention: We compared neonatal transmission rates between those neonates who experienced bonding versus those who were separated. Results: A total of 1989 women were screened for SARS-CoV-2, from which 86 tested positive. Out of 31 analyzed pregnancies, five women (16%) were admitted to ICU and required mechanical ventilation. From the remaining 26 (84%), 17 (65%) opted for rooming-in, 12 (46%) for STSC, and 16 (61%) fed the infants with breastmilk (11 direct breastfeedings and five pumped the breast milk). All neonatal tests for SARS-CoV-2 returned negative. Conclusion: Our results have illustrated that maternal bonding appears safe in neonates born to mothers that are SARS-CoV-2 positive.